Disinformation in the Post-Truth Era: Epistemological Constructs, Social Contagion, and the Role of the iField - Urs, Shalini R. (Journal of Information and Knowledge, 2024)
This paper examines the “post-truth era” focusing on fake news and disinformation, emphasising their role in undermining the foundational principles of science and society. It begins by distinguishing misinformation, disinformation, and malinformation, setting the stage for a theoretical framework that conceptualises disinformation through the lens of the Indian epistemological concept of Pramāṇa, Floridi’s Philosophy of Information, and Aristotle’s Theory of Deviance. Additionally, the paper posits that contagion theories, such as those by Le Bon and others, help explain the spread of disinformation in an era dominated by social networks, making a case for Social Network Analysis as a valuable tool. Practical strategies and tools to combat falsehoods are also offered. Finally, it argues that the field of information studies (iField) must address this crisis by incorporating relevant content into its curriculum and education.